2014
DOI: 10.4269/ajtmh.12-0657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Malnutrition on Children's Immunity to Bacterial Antigens in Northern Senegal

Abstract: Abstract. To evaluate immunity to vaccine-preventable diseases according to nutritional status, a longitudinal study was conducted in Senegalese children ages 1-9 years old. A linear regression analysis predicted that weight for age was positively associated with immunoglobulin G (IgG) response to tetanus toxoid in children born during the rainy season or at the beginning of the dry season. A relationship between village, time of visits, and levels of antibodies to tetanus showed that environmental factors pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Status pemberian ASI eksklusif tidak terdapat hubungan yang signifikan dengan kejadian stunting (39). Hal ini disebabkan oleh keadaan stunting tidak hanya ditentukan oleh faktor status pemberian ASI eksklusif, tetapi juga dipengaruhi oleh faktor lain seperti: kualitas Makanan Pendamping ASI (MP-ASI), kecukupan asupan gizi yang diberikan kepada anak setiap hari, serta status kesehatan bayi (40)(41)(42) anak TK (43)(44)(45)(46). Ini disebabkan bahan yang digunakan untuk imunisasi dasar telah melalui uji klinik sehingga tidak menyebabkan stunting.…”
Section: Kejadian Stuntingunclassified
“…Status pemberian ASI eksklusif tidak terdapat hubungan yang signifikan dengan kejadian stunting (39). Hal ini disebabkan oleh keadaan stunting tidak hanya ditentukan oleh faktor status pemberian ASI eksklusif, tetapi juga dipengaruhi oleh faktor lain seperti: kualitas Makanan Pendamping ASI (MP-ASI), kecukupan asupan gizi yang diberikan kepada anak setiap hari, serta status kesehatan bayi (40)(41)(42) anak TK (43)(44)(45)(46). Ini disebabkan bahan yang digunakan untuk imunisasi dasar telah melalui uji klinik sehingga tidak menyebabkan stunting.…”
Section: Kejadian Stuntingunclassified
“…We tentatively suggest that in rural Ethiopia the high frequency of environmental enteric dysfunction and high incidence of viral, bacterial and parasitic infection may adversely affect the DTHR test, including in non-malnourished children, by maintaining children in a state of chronic inflammation [ 22 , 34 , 46 48 ]. Also, despite not being wasted, the control group may have undiagnosed micronutrient deficiencies that can affect the DTHR [ 49 ]. These factors may also explain why many of the children did not have a BCG scar despite being BCG vaccinated.…”
Section: Main Textmentioning
confidence: 99%
“…Many studies have shown that, although current protocols for treating children with (acute) undernutrition reduce mortality, they do not rescue its long-term morbidities, including stunting, immune dysfunction, and neurodevelopmental abnormalities (Victora et al, 2008, Gaayeb et al, 2014, Kosek et al, 2013, Galler et al, 2012). For example, given the remarkable metabolic requirements of the neonatal brain, alterations in the normal postnatal development of the gut microbiota may trigger marked impairments in brain development and lead to persistent disorders of cognition.…”
Section: Undernutrition and Gut Microbiota Immaturitymentioning
confidence: 99%